Kondisi Terumbu Karang Di Kepulauan Seribu Dalam Kaitan Dengan Gradasi Kualitas Perairan [Water Quality Gradation Of Coral Reef At Seribu Island] - Pujiono Wahyu Purnomo; Ruswahyuni Ruswahyuni (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract The increasing of Jakarta land activies caused eutrophication, so that it changes species composition and decreasing of number of species. The sea within the high of eutrophication has correlation with the high growth of alga, depletion of oxygen and change of coral species composition. These researchs was done at coral reef ecosystem of Lancang Island, Pari Island and Payung Island, whereas there are part of Seribu Island Cluster. The aims of research was evaluating of nutrient enrichment effect to morphology and functional of coral reef condition. Morphology figures are showed by basic cover, whereas functional aspects are evaluated by zooxanthellae density. The results are showed that the high eutrophication is significantly correlated with main land of Java Island distance. The increasing of nutrient enrichment is significantly to change profile of coral reef and zooxanthellae densities.